Preparation and photoelectrochemical properties of CdS quantum dot‐sensitized ZnO nanotube arrays. Issue 6 (2nd June 2019) - Zhao, Wenyan; Tian, Chuanjin; Luo, Penghui; Hao, Bianlei; Xie, Zhipeng; Fu, Wuyou; Yang, Haibin
Abstract: CdS/ZnO nanotubes (NTs) arrays were synthesized on a transparent conductive glass (FTO) substrate by hydrothermal method, chemical bath etching and successive ionic layer adsorption and reaction (SILAR) method, which were used in semiconductor‐sensitized photoelectrochemical cells (PECs). The crystal structure, morphology and photoelectrochemical conversion properties of different photoanodes were investigated by X‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscope (TEM), high resolution transmission electron microscope (HRTEM), and electrochemical workstation. The results show a heterojunction has been formed between ZnO and CdS QDs. The ZnO NTs and CdS QDs played a remarkable controllability for PEC performances. The photoelectrochemical conversion efficiency of ZnO NTs photoanodes was 3 times that of ZnO nanorods (NRs) arrays photoanodes. After sensitization of CdS quantum dots, the photoelectrochemical conversion efficiency of CdS/ZnO NRs was improved by 7 times and the CdS/ZnO NTs was increased by 4 times. These results demonstrate that the CdS/ZnO core‐shell structure can provide a facile and compatible frame for the potential applications in nanotube‐based solar cells.